<span>A) x+y+z=23
B) y+z=14
C) z=9
Since z = 9 then
A) x + y = 14
B) y = 5
A) </span><span><span>x + y+ z=23</span>
A) x + 5 + 9 = 23
A) x = 9
</span>
Answer:
Angle 1,4 and 7
Step-by-step explanation:
I know I know
Answer:
C
Step-by-step explanation:
A, B are wrong since 8,795 is a constant, it doesn’t change;
D is wrong since it is the starting cost, not total cost
Answer:
![h(x) + g(x) = x^{2} + 4x - 3](https://tex.z-dn.net/?f=h%28x%29%20%2B%20g%28x%29%20%3D%20x%5E%7B2%7D%20%2B%204x%20-%203)
Step-by-step explanation:
h(x) + g(x) = ![(x^{2} + 6x) + (-2x - 3)](https://tex.z-dn.net/?f=%28x%5E%7B2%7D%20%2B%206x%29%20%2B%20%28-2x%20-%203%29)
![x^{2} + 4x - 3](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2B%204x%20-%203)